P004 Solriamfetol for excessive daytime sleepiness in obstructive sleep apnoea: a randomised controlled trial. (19th November 2019) - Schweitzer, Paula K; Mayer, Geert; Rosenberg, Russell; Zammit, Gary K; Gotfried, Mark; Chen, Dan; Carter, Lawrence P; Wang, Hao; Black, Jed; Malhotra, Atul; Strohl, Kingman P
Abstract : Introduction: Obstructive sleep apnoea (OSA) is often associated with persistent excessive daytime sleepiness (EDS) despite sleep apnoea therapy. There are currently no approved treatments in the European Union for the treatment of EDS in this population. Solriamfetol (formerly JZP-110), a dopamine and norepinephrine reuptake inhibitor, has been approved in the United States to improve wakefulness in adults with EDS associated with narcolepsy (75–150 mg) or OSA (37.5–150 mg). A Marketing Authorisation Application for these indications is under review with the European Medicines Agency. This study evaluated the efficacy and safety of solriamfetol for treatment of EDS in participants with OSA with current or prior sleep apnoea treatment. 1 Methods: In this double-blind, placebo-controlled, parallel-group phase 3 trial, participants with OSA and associated EDS were randomly assigned to solriamfetol 37.5 mg, 75 mg, 150 mg, or 300 mg or placebo for 12 weeks. Results: Of 476 randomised participants, 459 were included in the prespecified efficacy analyses. Co-primary endpoints (Maintenance of Wakefulness Test sleep latency, Epworth Sleepiness Scale score) were met at all solriamfetol doses (P<0.05), with dose-dependent effects observed at week 1 and maintained over the study duration. All doses except 37.5 mg resulted in significantly higher percentages of participants reporting improvement on Patient Global Impression of Change (key secondary endpoint; P<0.05). Adverse events (AEs) were reported in 47.9% of placebo- and 67.9% of solriamfetol-treated participants; 5 participants experienced serious AEs (2 [1.7%] placebo, 3 [0.8%] solriamfetol); none were deemed related to study drug. The most common AEs with solriamfetol were headache (10.1%), nausea (7.9%), decreased appetite (7.6%), anxiety (7.0%), and nasopharyngitis (5.1%). Discussion: Solriamfetol significantly improved wakefulness and reduced sleepiness in participants with OSA and EDS. Most AEs were mild or moderate. Support: Jazz Pharmaceuticals. Reference: Schweitzer PK, et al. Am J Respir Crit Care Med 2019:199(11)1421–1431.